2019
DOI: 10.18584/iipj.2019.10.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Community Setting as a Determinant of Health for Indigenous Peoples Living in the Prairie Provinces of Canada: High Rates and Advanced Presentations of Tuberculosis

Abstract: Indigenous Peoples in Canada experience disproportionately high tuberculosis (TB) rates, and those living in the Prairie Provinces have the most advanced TB presentations (Health Canada, 2009). The community settings (i.e., urban centres, non-remote reserves, remote reserves, and isolated reserves) where Indigenous Peoples live can help explain high TB rates. Through qualitative description, we identify how community setting influenced Indigenous people’s experiences by (a) delaying accurate diagnoses; (b) per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 38 publications
(43 reference statements)
1
16
0
1
Order By: Relevance
“…[19][20][21][22] Three publications reported on the qualitative component of a mixed-methods study [23][24][25] and 2 reported on both quantitative and qualitative components of a mixed method. 26,27 One was a focused ethnography, 28 one a qualitative description study, 29 one used community-based participatory research methods, 30 another relied on citizen panels (deliberative methods), 31 and one was an interpretive phenomenology analysis. 32 Six publications reporting on 5 studies collected data through interviews.…”
Section: Study Design Data Collection and Methods Of Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…[19][20][21][22] Three publications reported on the qualitative component of a mixed-methods study [23][24][25] and 2 reported on both quantitative and qualitative components of a mixed method. 26,27 One was a focused ethnography, 28 one a qualitative description study, 29 one used community-based participatory research methods, 30 another relied on citizen panels (deliberative methods), 31 and one was an interpretive phenomenology analysis. 32 Six publications reporting on 5 studies collected data through interviews.…”
Section: Study Design Data Collection and Methods Of Analysismentioning
confidence: 99%
“…32 Six publications reporting on 5 studies collected data through interviews. 21,23,25,[28][29][30] Two publications collected data using interviews and focus groups 19,22 and 1 used interviews with individuals and groups. 24 Two publications collected data using focus groups 20,26 and 1 publication collected data through community panels.…”
Section: Study Design Data Collection and Methods Of Analysismentioning
confidence: 99%
See 3 more Smart Citations